Chemical Monitoring of Metal Pollutants Along the Mumbai Coastline - D. Irani, Shahin; Prabhu, D.V. (Asian Journal of Chemistry, 2012)
Industrial effluents introduce several metal pollutant into the marine waters around the island city of Mumbai. Heavy metals like iron, chromium, copper, zinc and lead are potentially hazardous to aquatic life. Metal pollutant were monitored at 10 sites along the Mumbai coastline during pre rainy season (June), rainy season (September) and winter (December). The water samples were collected using standard methods. Calcium and magnesium were estimated complexometrically using Erichrome Black T and Patton and Reeder indicators. Iron, chromium and cadmium were estimated spectrophotometrically at 510, 540 and 520 nm respectively. The high cadmium content in the month of September at almost all the city beach fronts has been attributed to the influx of cadmium salts due to the immersion of the clay idols of Lord Ganesh during the religious festivals of Ganapati. The chloride content was also monitored iodometrically and seasonal variation explained. The variation of the metal content with seasons has been explained and the chemical quality of the coastal waters was compared with the WHO and ISI standards for potable water. It was concluded that the Mumbai coastal water have a high dose of metal contaminants and hence cannot sustain acquatic life.